Reconceptualizing curriculum development : inspiring and informing action - Henderson, James G. (Studies in Curriculum Theory Series, 2015)
Reconceptualizing Curriculum Development provides accessible, clear guidance on curriculum problem solving and educational leadership through the practice of a synoptic curriculum study. This practice integrates three influential interpretations of curriculum--curriculum as deliberative artistry, curriculum as complicated conversation, and curriculum as currere--with John Dewey's lifetime work on reflective inquiry. At its heart, the book advances a way of studying as a way of living with reference to the question: How might I live as a democratic educator? The study guidance is organized as an open-ended scaffolding of three embedded reflective inquiries informed by four deliberative conversations. Study recommendations are provided by a carefully selected team. The field-tested study-based approach is illustrated through a multi-layered, multi-voiced narrative collage of four experienced teachers' personal journeys of understanding in a collegial study context. Applying William Pinar's argument that a "conceptual montage" enabling teachers to lead complicated conversations should be the focus for curriculum development in the field's current 'post-reconceptualist' moment, the book moves forward the educational aim of facilitating a holistic subject/self/social understanding through the practice of a balanced hermeneutics of suspicion and trust. It closes with a discussion of cross-cultural collaboration and advocacy, reflecting the interest of curriculum scholars in a wide range of countries in this study-based, lead-learning approach to curriculum development